2019
DOI: 10.5603/ocp.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Complete pathological remission after palliative therapy with sorafenib in hepatocellular carcinoma — case report

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primary malignant liver cancer. The five-year overall survival (OS) in men diagnosed with HCC does not exceed 9%. Patients (pts) with advanced disease are treated with sorafenib (multikinase inhibitor). In randomised trials the OS advantage was within the range of three months for sorafenib. Stabilisation of disease was achieved in 71% of patients, and no case of CR was reported. We present a case of 60-year-old patient with locally advanced cT3aN0M0 (stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the ALICE-1 study suggested that genetics may play an important role in the response to sorafenib, as certain genotypes within VEGF polymorphisms are associated with a significantly higher OS [32]. Despite unsatisfactory responsive rates observed in clinical trials, rare case reports describe patients who achieved a significant tumor size reduction, in whom surgical approach became feasible [33,34]. Nevertheless, in a large retrospective analysis by Rimola et al, out of 1119 HCC patients treated with sorafenib, only 12 (1%) were finally classified as complete responders.…”
Section: Sorafenibmentioning
confidence: 99%
“…Moreover, the ALICE-1 study suggested that genetics may play an important role in the response to sorafenib, as certain genotypes within VEGF polymorphisms are associated with a significantly higher OS [32]. Despite unsatisfactory responsive rates observed in clinical trials, rare case reports describe patients who achieved a significant tumor size reduction, in whom surgical approach became feasible [33,34]. Nevertheless, in a large retrospective analysis by Rimola et al, out of 1119 HCC patients treated with sorafenib, only 12 (1%) were finally classified as complete responders.…”
Section: Sorafenibmentioning
confidence: 99%